Mechanisms of HIV Transcriptional Regulation by Drugs of Abuse - Tyagi, Mudit; Bukrinsky, Michael; L. Simon, Gary (Current HIV Research, 2016)
Background: There is a strong correlation between the use and abuse of illicit drugs and the spread of Human Immunodeficiency Virus (HIV). It is well established that illicit drugs users are a high risk population for infection with HIV with an increased rate of HIV transmission and replication. Cocaine, amphetamine, methamphetamine, heroin and morphine stand out as the most frequently abused illicit drugs and their use correlates well with HIV infection and AIDS progression. Notably, the high incidence of HIV infection in illicit drug abusers is primarily due to high risk activities such as needle sharing and unprotected sex. Several studies have also demonstrated that drugs of abuse increase viral RNA concentrations by enhancing HIV replication, in particular in the central nervous system (CNS). The CNS is a common target for both drugs of abuse and HIV, and their synergistic action accelerates neuronal injury and cognitive impairment. In order to generate complete genomic transcripts, HIV gene expression has to progress through both the initiation and elongation phases of transcription, which requires coordinated action of different transcription factors. Conclusion: In this review, we will provide the latest updates of the molecular mechanisms that regulate HIV transcription and discuss how drugs of abuse, such as cocaine, amphetamine, methamphetamine, heroin and morphine, modulate those mechanisms to upregulate HIV transcription and eventually HIV replication.
Keywords: epigenetics